Effect of Roasting on the Antioxidant Activity, Phenolic Composition, and Nutritional Quality of Pumpkin (Cucurbita pepo L.) Seeds - Peng, Mengyao; Lu, Dan; Liu, Jie; Jiang, Bo; Chen, Jingjing (Frontiers in Nutrition, 2021)
In recent years, with the increasing awareness of health concerns and environment protection needs, there is a growing interest for consumers to choose plant-based food diets compared with those made from animal origin. Pumpkin seed is an excellent dietary source for protein, oil and some essential micronutrients. Raw pumpkin seed may have a compromised flavor, color, as well as digestibility. Therefore, the objective of present study is to study the influence of roasting (120, 160, and 200°C for 10 min) on the phenolics content, flavonoids content, antioxidant property, fatty acids and volatile matter composition, as well as protein profile of pumpkin seeds. Our results indicated that, total phenolic compounds, total flavonoids content, as a consequence, total antioxidant capacity increased as the roasting temperature increased. Maillard reaction products and lipid peroxidation products were identified, especially from those pumpkin seeds roasted at high temperature. In the meantime, the composition and content of fatty acids did not change significantly after roasting. The results of electrophoresis and particle size analysis showed that the optimum roasting temperature was 160°C to obtain protein with better nutritional quality. The findings of this study may contribute to the utilization of pumpkin seed component in plant-based diets with increased nutritional quality.